Høj opsparing under corona var drevet af restriktioner snarere end forsigtige forbrugere - Svend Greniman Andersen; Rasmus Mose Jensen; Nicolai Risager Christensen (Danmarks Nationalbank, 2021)
– Households' savings increased significantly during the first wave of the corona pandemic in Denmark and several other countries. This Economic Memo finds that the higher savings in Denmark were driven by restrictions rather than precautionary consumers. Precautionary savings have so far been relatively limited and smaller than during the financial crisis.
Keywords: 330; Sparen; Konsumentenverhalten; Coronavirus; Dänemark